2020
DOI: 10.1177/1609406920933398
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, Gay, and Bisexual (LGB) Young Adults’ Relational Well-Being Before and After Taiwanese Legalization of Same-Sex Marriage: A Qualitative Study Protocol

Abstract: In 2019, Taiwan became the first country in Asia to legalize same-sex marriage. Such an historic shift in the legal landscape toward marriage equality in Taiwan presents a timely and unique opportunity to investigate the interplay of a lesbian, gay, and bisexual (LGB)-affirmative policy (i.e., marriage equality) and the well-being of LGB people. Existing quantitative studies on same-sex marriage have yielded compelling evidence about its positive effects on LGB individuals’ psychosocial health. However, no res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Adolescence is a transitional stage during which adolescents discover their identity, and for LGBTQ adolescents, it is also the period during which they gain an awareness of their own gender identity and sexual preference (Prock and Kennedy, 2020). Research has shown shifting relationships throughout adolescence and young adulthood, with a corresponding change in commitment to friends and social classes apart from the family, as well as to entities such as education, colleges, religious or political communities (Huang, 2020;Jordan, 2020). Recognition by support communities is a powerful preventive mechanism for LGBTQ children and adolescents (Call et al, 2021).…”
Section: Impact On Psychological Wellbeing Among Lesbian Gay Bisexual...mentioning
confidence: 99%
“…Adolescence is a transitional stage during which adolescents discover their identity, and for LGBTQ adolescents, it is also the period during which they gain an awareness of their own gender identity and sexual preference (Prock and Kennedy, 2020). Research has shown shifting relationships throughout adolescence and young adulthood, with a corresponding change in commitment to friends and social classes apart from the family, as well as to entities such as education, colleges, religious or political communities (Huang, 2020;Jordan, 2020). Recognition by support communities is a powerful preventive mechanism for LGBTQ children and adolescents (Call et al, 2021).…”
Section: Impact On Psychological Wellbeing Among Lesbian Gay Bisexual...mentioning
confidence: 99%
“…Data for this study came from a larger qualitative investigation of the effects of same‐sex marriage in Taiwan (Huang, 2020) in which parental responses to and acceptance of their child's sexual identity were part of the study focus. The full project comprised two waves of interviews with the same participants and involved both LGB young adults and one of their parents.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of family life and family-related welfare, Taiwan's legalised same-sex marriage has provided more options for LGBTQ+ individuals to develop their intimate and family relations (Huang and Hang, 2023). Importantly, gaining legal marital status grants same-sex couples the rights associated with families and enables them to access welfare benefits.…”
Section: Welfare Outcomesmentioning
confidence: 99%